ANALYSIS OF THE EFFECT OF MACROECONOMIC POLICY ON THE STATE BUDGET DEFICIT IN INDONESIA FROM AN ISLAMIC ECONOMIC PERSPECTIVE (2007-2024) - Hoirun Nisa, Desi Nabila; Zulaikah, Zulaikah; Kurniawan, Agus (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
The state budget deficit is a condition where expenditures exceed revenues. In Indonesia, there has been a deficit almost every year. If this condition continues, the main risks are an increase in national debt and economic instability, which will have an impact on the welfare of the people. The purpose of this study is to analyze the factors that influence the state budget deficit. The variables studied are Government Securities, Tax Revenue, and Interest Rates. The data used is time series data from 2007 to 2024. The approach applied is the Error Correction Model (ECM), which aims to examine long-term and short-term effects. According to this study, government securities do not have a significant short-term effect but have a considerable positive long-term impact. The long-term and short-term effects of the tax revenue variable are significantly negative. Meanwhile, the interest rate variable has no significant effect on either time period. The government is expected to utilize this research as a guide in formulating policies. This research helps academics expand their knowledge and serves as a source of literacy and information for the general public.